Fluctuating Fund-Balance System as Control of Petty Cash Disbursements Based on Accounting Information System - Rohim, Nadhira Irfanaja; Wijaya, Raden Muhammad Syah Arief Atmaja (Universitas Prasetiya Mulya, 2024)
This research aims to describe the importance of accounting information systems in controlling the petty cash disbursements of hotel companies. This research method uses a descriptive qualitative approach. The location of this research is Hotel X, a three-star hotel in Surabaya. Data collection methods in this research used interviews, observation, and documentation. The research data analysis technique consists of stages of data collection, data presentation, data reduction, verification, and conclusion. The accounting information system at Hotel X implements two systems for controlling petty cash disbursements based on the petty cash fund holder, namely petty cash disbursements by the front office petty cash fund holder and petty cash disbursements by the general cashier petty cash fund holder. The fluctuating fund-balance system provides a well-structured system for hotel companies to control petty cash disbursements. The implications of this research, regarding the fluctuating fund-balance system in controlling petty cash disbursements, can influence business actors in making it easier to record transactions more accurately and transparently. The limitations of this research lie in the location of the research conducted at a three-star hotel company, making it possible to have differences in systems that exist in other star hotel companies.